Application of Mathematics in Economics: Demand and Supply Functions - Melani (GoResearch - Research & Publishing House, 2023)
This article aims to review the application of mathematics in economics regarding the function of demand and supply and market stability. This study uses exploratory methods and data is collected through literature study techniques. The use of demand, supply and market balance problems can be in the form of mathematical concepts in a two-variable linear equation system and the solutions are formed through elimination, substitution, and graphic methods. The study findings explain that the correlation between demand and supply functions is formed from the mathematical concept of linear functions and equations of two variables.